1989
DOI: 10.1007/bf02024324
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different oestrogen doses on final height reduction in girls with constitutional tall stature

Abstract: The effects of different doses of oestrogens in constitutionally tall girls were evaluated in two centres for paediatric endocrinology. In one centre, 38 girls were treated with a high oestrogen dose of 0.3 to 0.5 mg ethinyloestradiol (EE) daily. In the other, 44 girls received a comparably low dose of 0.1 mg EE per day. Height prediction (HP), chronological age (CA), and height at the onset of treatment were comparable in both groups. Although the duration of treatment was significantly longer in those receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
2
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 26 publications
3
16
2
1
Order By: Relevance
“…All girls experienced spontaneous menstrual bleeding within 3 to 22 weeks after termination of therapy. The same was observed in most later follow-up studies in which first menstruation was reported within 1-6 months after cessation of treatment, in most cases even after the first month (103,114,127,130). Amenorrhea of longer than 6 months after cessation of height-reductive therapy was reported in about 5% of the cases (175).…”
Section: The Hypothalamo-pituitary-gonadal Axis and Menstrual Cyclessupporting
confidence: 74%
See 4 more Smart Citations
“…All girls experienced spontaneous menstrual bleeding within 3 to 22 weeks after termination of therapy. The same was observed in most later follow-up studies in which first menstruation was reported within 1-6 months after cessation of treatment, in most cases even after the first month (103,114,127,130). Amenorrhea of longer than 6 months after cessation of height-reductive therapy was reported in about 5% of the cases (175).…”
Section: The Hypothalamo-pituitary-gonadal Axis and Menstrual Cyclessupporting
confidence: 74%
“…Some reports are in favor of this finding (109,122,123,125) while others observed no difference (103,107,128,130). In our study (101), premenarcheal girls seem to benefit more from therapy than postmenarcheal girls.…”
Section: B Height Reductioncontrasting
confidence: 39%
See 3 more Smart Citations